Effect of L-Citrulline from Watermelon Seed Extract as a Green Corrosion Inhibitor against the Corrosion Rate of Pipe Steel API 5L X65 - Bambang Widyanto (Mesin, 2018)
API 5L X65 carbon steel is used in many industries, especially as oil and gas pipelines. However, this carbon steel pipe is vulnerable to corrosion at the inner surface owing to the flow of oil that is a multiphase system and contains dissolved salts. The corrosion phenomenon of the internal surface can be prevented by using an inhibitor. Most of the inhibitors used in industry are composed of compounds that are toxic and environmentally unfriendly. Consequently, the use of a natural inhibitor is at the forefront of corrosion inhibition studies. This study examines the efficiency of watermelon seed extract as an inhibitor before and after the addition of methyl ethyl glycol (MEG). The influence of L-citrulline from watermelon seed extract (WMSE) and MEG on the inhibition of corrosion of carbon steel in 3% NaCl containing acetic acid saturated by CO2 at room temperature was investigated by the immersion test, polarization test, electrochemical impedance spectroscopy (EIS), and surface analysis by scanning electron microscopy (SEM). According to the experiment results, the corrosion rate increased with the acid concentration and the effect of CO2. The corrosion rate can be inhibited by MEG, WMSE, and mixtures thereof. In comparison with 3% NaCl media containing acetic acid (HAc) 3360 ppm in saturated CO2 at room temperature, the inhibition efficiency of WMSE using polarization and EIS methods were 93.54% and 95.89%, respectively. However, based on the immersion test results, the inhibition efficiency was decreased. The inhibition efficiency of WMSE dropped after 120 hours of the immersion process by almost 40fold to 2.38%, while the efficiency of MEG was able to inhibit the surface by 80.48%. The mechanism of the inhibition by a WMSE molecule is through a chemisorption process, which forms a complex bond and generates a passive layer of Fe-WMSE.